2019
DOI: 10.33366/jast.v3i2.1471
|View full text |Cite
|
Sign up to set email alerts
|

Teknik Design Labeling Pengembangan Model Kemasan Keripik Salak Pondoh oleh Wanita Tani Srikandi dan Karya Bhakti

Abstract: Salak pondoh merupakan salah satu jenis buah salak yang cukup diminati masyarakat. Kegiatan pengabdian berupa Iptek bagi Masyarakat (IbM) kepada kelompok wanita tani Srikandi dan Karya Bhakti dilakukan dengan tujuan untuk meningkatkan keterampilan produksi, teknik pengemasan, design labelling dan pemasaran guna menunjang omset penjualan dan nilai tambah pada keripik buah salak pondoh yang sedang mereka usahakan. Metode yang digunakan dalam pengabdian ini adalah metode pelatihan, pendampingan dan pendidikan kep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The packaging of a product can be used as a medium of communication between producers and consumers to form an image (Indrihastuti et al, 2019). Herawati & Listyawati (2017) revealed that through labels on packaging manufacturers can provide information regarding quality, brand, production code, legality, instructions for use or presentation.…”
Section: Introductionmentioning
confidence: 99%
“…The packaging of a product can be used as a medium of communication between producers and consumers to form an image (Indrihastuti et al, 2019). Herawati & Listyawati (2017) revealed that through labels on packaging manufacturers can provide information regarding quality, brand, production code, legality, instructions for use or presentation.…”
Section: Introductionmentioning
confidence: 99%